A 1‐D morphodynamic model of postglacial valley incision. Issue 11 (12th November 2015) - Tunnicliffe, Jon F.; Church, Michael
Abstract: Chilliwack River is typical of many Cordilleran valley river systems that have undergone dramatic Holocene degradation of valley fills that built up over the course of Pleistocene glaciation. Downstream controls on base level, mainly blockage of valleys by glaciers, led to aggradation of significant glaciofluvial and glaciolacustrine valley fills and fan deposits, subsequently incised by fluvial action. Models of such large‐scale, long‐term degradation present a number of important challenges since the evolution of model parameters, such as the rate of bedload transport and grain size characteristics, are governed by the nature of the deposit. Sediment sampling in the Chilliwack Valley reveals a complex sequence of very coarse to fine textural modes. We present a 1‐D numerical morphodynamic model for the river‐floodplain system tailored to conditions in the valley. The model is adapted to dynamically adjust channel width to optimize sediment transporting capacity and to integrate relict valley fill material as the channel incises through valley deposits. Sensitivity to model parameters is studied using four principal criteria: profile concavity, rate of downstream grain size fining, bed surface sand content, and the timescale to equilibrium. Model results indicate that rates of abrasion and coarsening of the grain size distributions exert the strongest controls on all of the interrelated model performance criteria. While there are a number of difficulties in satisfying all model criteria simultaneously, results indicate that 1‐D models of valley bottom sedimentary systems can provide a suitable framework for integrating results from sediment budget studies and chronologies of sediment evacuation established from dating. Key Points: Degrading postglacial gravel river is influenced by composition of valley fill One‐dimensional model of channel and floodplain storage helps to constrain evacuation rates Evaluation of model using three or more criteria provides process insights